Nationalism in Balinese Kiaiâ€™s Poems: A Discourse Analysis - Rizal, Efri Arsyad; Rahman, Luthfi; Fa'atin, Salmah (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2020)
The paper discusses the teachings of nationalism by KHR. Ahmad al-Hadi bin Dahlan al-Falaky in his poems. This research tried to explore aspects of local wisdom and accordingly to figure out the values of nationalism within the poems of a traditional Kiai living in the Balinese society where the majority were Hinduâ€™s people. Data were primarily sourced and collected from â€œKumpulan Syaâ€™ir KHR. Ahmad al-Hadi bin Dahlan al-Falaky (1895-1976).â€It uses discourse analysis to reveal the meaning of the poems. This finding shows that the poems firmly teach and emphasize the values of nationalism to society. In this regard, such values are vital to fostering the peopleâ€™s nationalism for living side by side and in harmony with â€œthe othersâ€ in the Balinese local context to the Indonesian national context and dealing with the challenging globalized ways of life.